PROFIL KEMAMPUAN MEMBACA DAN MENULIS KELAS RENDAH SISWA SD DI ERA PANDEMI COVID-19 - Muh Luqman Arifin; Lilis Sulistia Ningsih; Mahmudin Mahmudin (Nusantara Hasana Berdikari, 2022)
The purpose of this study was to determine the achievement of low-grade reading and writing learning outcomes at SD Negeri Adisana 03 Bumiayu during the Covid-19 pandemic. The research method used is qualitative research with a phenomenological approach. The data collection techniques used are tests, interviews, and documentation. The validity of the data in this study uses source triangulation. The subjects in this study were teachers and grade I students of SD Negeri Adisana 03 Bumiayu. The results showed that the ability to read and write was 95% more than 75%, with an average score of 81.56 so that it had reached KKM. The achievement of learning outcomes of reading and writing skills of low-grade students at SD Negeri Adisana 03 Bumiayu is included in the high (good) category.